/ The silence of the languages: the possibility of translating a poem - Silva, Maria das Graças Gomes Villa da (Revista de Letras, 2007)
Neste ensaio, retoma-se a afirmação do tradutor Sergio Augusto de Andrade sobre a impossibilidade de se traduzir um poema. Por meio da nação derridiana de significante e significado, que inclui a existência de uma presença-ausência na origem do significado, tenta-se demonstrar que a tradução é possível, em razão do momento de disseminação/contaminação do significado ou suplemetaridade do signo.In this essay, it is considered the statement of the translator Sergio Augusto de Andrade about the impossibility of translating a poem. Applyng the derridean notion of the sifnifier and the signified, which includes the idea if an undecidable presence-absence at the original of the meaning, it is discussed that the translation of a poem is possible due to the movement of dissemination / contamination of the meaning or suplemetary of the sign.